(untitled) (Revista Electrónica REDINE, 2021)
The journal TEORÍAS, ENFOQUES Y APLICACIONES EN LAS CIENCIAS SOCIALES (TEACS), a scientific, refereed and indexed journal of semi-annual publication, open access and free, published in the Dean of Economic and Business Sciences of the Universidad Centroccidental Lisandro Alvarado (UCLA), Venezuela. Dedicated to the development and promotion of research in the area of ​​Social Sciences, with special interest in areas related to Management and Accounting. Post.